المعقول والغير معقول في توقعات مستخدمي القوائم المالية من مراجع الحسابات (دراسة وإقتراح الحلول) - خالدي, رشيدة (جامعة الوادي - University of Eloued, 2021)
دائما عند تقديم خدمة معينة يكون هناك توقع من الأطراف المستفيدة من هذه الخدمة، حيث أن تقديم خدمات المراجعة من قبل مراجع الحسابات يقابله توقعات عديدة من قبل مستخدمي القوائم المالية وهذا ما ينشئ لنا فجوة التوقعات في مهنة المراجعة، إلا أن على مراجع الحسابات عدم أغفال هذه التوقعات حتى يتمكن من أداء عملية المراجعة بأعلى درجات الكفاءة المهنية والوصول إلى أكبر قدر ممكن من التوافق بين مسؤولياته وتوقعات المجتمع المالي، نحاول من خلال دراستنا اظهار ما هو معقول وغير معقول لتوقعات مستخدمي القوائم المالية، وذلك من خلال دراسة لهذه التوقعات وفي المقابل تقديم مجموعة من الحلول التي من شأنها تقليص هذه الفجوة، حيث خلصت الدراسة إلى أن هناك توقعات تندرج تحت مسؤوليات مراجع الحسابات وتوقعات غير معقولة ترجع إلى جهل بعض أفراد المجتمع المالي لمسؤوليات مراجع الحسابات. Always when a certain service is provided, there is an expectation from the parties benefiting from this service, as the provision of audit services by the auditor is offset by many expectations from the users of the financial statements, and this creates an expectation gap for us in the audit profession, but the auditor should not neglect these Expectations In order to be able to perform the audit process with the highest degree of professional competence and reach the greatest possible compatibility between his responsibilities and the expectations of the financial community, we try through our study to show what is reasonable and unreasonable for the expectations of users of financial statements, through a study of these expectations and in return providing a set of Solutions that would reduce this gap, as the study concluded that there are expectations that fall under the responsibilities of the auditor and unreasonable expectations due to the ignorance of some members of the financial community of the responsibilities of the auditor
Reasonable and Unreasonable Expectations of Users of Financial Statements From The Auditor (Studying and Suggesting Solutions)
مقال
Keywords: مراجع الحسابات؛ مستخدمي القوائم المالية؛ فجوة التوقعات.; auditor; users of financial statements; Expectations Gap.